ICT's Role in e-Governance in India and Malaysia: A Review - Jasni, Mohamad Zain; Deka, Ganesh Ch; Mahanti, Prabhat (AICIT, Korea, 2012)
Information and Communication Technologies (ICTs) play a key role in Development and Economic growth of the Developing countries of the World. Political, Cultural, Socio-economic Developmental and Behavioral decisions today rests on the ability to access, gather, analyze and utilize Information and Knowledge. Government of India is having an ambitious objective of transforming the citizengovernment interaction at all levels to by the electronic mode by 2020.Similarly according to the Vision 2020-The Way Forward presented by His Excellency YAB Dato' Seri Dr Mahathir Mohamad at the Malaysian Business Council "By the year 2020, Malaysia can be a united nation, with a confident Malaysian society, infused by strong moral and ethical values, living in a society that is democratic, liberal and tolerant, caring, economically just and equitable, progressive and prosperous, and in full possession of an economy that is competitive, dynamic, robust and resilient". This paper presents a comparative study and review relating to e-Governance and application of ICT development between India and Malaysia.